Forum Introduction: Reflections on the Fiftieth Anniversary of Erving Goffman’s Stigma - Brune, Jeffrey; Garland-Thomson, Rosemarie; Schweik, Susan; Titchkosky, Tanya; Love, Heather (Disability Studies Quarterly, 2014)
The plenary session at SDS 2013 on “Reflections on the Fiftieth Anniversary of Stigma” marked the fiftieth anniversary of Erving Goffman’s Stigma, which remains one of the most cited and influential works in the field. The panelists, whose essays appear in this forum, discuss Stigma’s origins and uses over the past decades, how the book has affected their own research and understandings of disability, and what role Stigma might play as disability studies continues to evolve. Each of the five essays in its own way answers one central question: whether and how Goffman’s work remains useful as we move the field forward.